Age‐related water uptake patterns of alpine plantation shrubs in reforestation region of Qinghai–Tibetan Plateau based on stable isotopes. Issue 1 (8th November 2018) - Wu, Huawu; Li, Xiao‐Yan; Li, Jing; Zhang, Cicheng; He, Bin; Zhang, Siyi; Sun, Wei
Abstract: Sea buckthorn ( Hippophae rhamnoides L.) plantations play crucial roles in the prevention of soil erosion and control of desertification on the Qinghai–Tibetan Plateau; however, the limited information on the age‐related water uptake patterns of H. rhamnoides and their relationships with associated grasses species weakens our understanding of how these factors influence the management of H. rhamnoides plantations. Therefore, this study investigated the seasonal variations in water uptake patterns of different‐aged H. rhamnoides and their associated species via stable isotopes and leaf water potential analyses. The model results showed that seedling (Hs) and juvenile (Hj) H. rhamnoides extracted water mainly from shallow and middle soil layers throughout the growing seasons, whereas mature H. rhamnoides (Hm) exhibited high plasticity, shifting water source between shallow soil water and groundwater when the former become less available. By contrast, the associated grasses ( Taraxacum mongolicum, Thermopsis lanceolata, and Polygonum sibiricum ) mainly absorbed shallow soil water across the whole growing seasons, suggesting that direct competition for shallow soil water occurred between grasses and H. rhamnoides . In addition, the obviously higher δ 13 C values of Hj with more negative predawn (mean Ψpd, −1.37 MPa) and midday (mean Ψmd, −2.23 MPa) leaf water potential indicated the Hj experienced greater water stress relative to Hs and Hm. These results provide new understanding of the seasonal water use strategies of different‐aged H. rhamnoides, which will be important for the successful management of plantations in this region.